Dampak Sosial Media Terhadap Dinamika Masyarakat Indonesia: Analisis Konseptual Dan Studi Literatur - Rasyidin, Nikita; Irwansyah (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
Social media has become an integral part of Indonesian people's lives, changing the way they interact, communicate and obtain information. This article aims to carry out a conceptual analysis and literature study regarding the impact of social media on the dynamics of Indonesian society, with a focus on the case of children who use gadgets in their diet. In the conceptual analysis, this research considers the theoretical framework related to the influence of social media on society, including social, psychological and cultural aspects. The results of the conceptual analysis show that children's use of gadgets in the context of social media can have a significant impact on their eating patterns, mental health and social development. The literature study illustrates a number of findings from previous research, especially in the context of children and gadget use. The results of literature studies indicate that excessive use of gadgets can disrupt children's healthy eating patterns, increase the risk of obesity, and reduce their social interaction time in physical environments. This article highlights the need for a better understanding of the impact of social media on Indonesian society, particularly in the context of children's eating patterns. The implications of this research can make an important contribution to the development of educational strategies and policies that support balanced social media use, children's health, and the development of society as a whole. Further research and collaboration between various stakeholders is needed to overcome the negative impacts and maximize the positive benefits of social media use in Indonesian society.